Effect of salinity stress on plant growth and root yield of carrot - Jahan, I; Hossain, MM; Karim, MR (Progressive Agriculture, 2020)
This study was carried out at Horticulture Farm of Bangladesh Agricultural University, Mymensingh to evaluate the effects of different levels of NaCl salinity on plant growth and root yield of two carrot varieties during the period from November, 2016 to February, 2017. Four levels of NaCl salt concentration viz., 0 (Control), 50, 100 and 150 mM and two varieties of carrot namely Shundori and Kuruda were used for this pot experiment. The two-factor experiment was laid out in randomized complete block design with three replications. The yield and yield components varied significantly between two carrot varieties and intensity of salt concentration. The maximum plant height (33.92 cm), length of leaves (14.51 cm), fresh weight of leaves (9.62 g), percent dry matter content of leaves (21.25 %), length of root (9.05 cm), diameter (11.24 cm), dry matter content of roots (18.18 %) were produced by Shundori. On the other hand, maximum water content of leaves (80.89 %), water content of roots (84.57 %) and weight of roots (10.76 g) were exhibited by Kuruda. Most of the studied parameters showed decreasing trends with the highest level of salinity (200 mM NaCl) producing lowest weight of roots (3.93 g). In case of combined effects of variety and salt concentrations, Kuruda with control condition produced maximum weight of roots (20.62 g) while the minimum weight of roots (3.53 g) was obtained by the combination of Kuruda with the highest level of salt concentration (200 mM NaCl). The result of the experiment revealed that the salinity stress significantly reduced all studied parameters at 100 mM and 150 mM as compared to control and 50 mM NaCl. Therefore, it can be concluded that the variety of Kuruda was found as relatively salt tolerant than Shundori. Progressive Agriculture 30 (3): 263-274, 2019